2018
DOI: 10.3390/app8091591
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanism of the Dispersion Behavior of Polymer-Modified Rejuvenators in Aged Asphalt Material

Abstract: Polymer-modified rejuvenator has a different composition and dispersion behavior to traditional rejuvenators. The objective of this study was to investigate the micromechanism of polymer-modified rejuvenators on the behavior of aged asphalt binder. Firstly, gel permeation chromatography (GPC) analysis was conducted to determine the dispersion effectiveness. Secondly, the dispersal behavior of polymer-modified rejuvenators was studied by means of atomic force microscopy (AFM) and scanning electron microscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 26 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…et al and Bilema, M. et al [17][18][19] surveyed the influence of rejuvenator content on penetration, softening point and ductility of recycled asphalt. Researchers investigated the microscopic mechanism of aged asphalt with rejuvenator, and it was found that the composition of aged asphalt changed by the rejuvenator, the light components decreased and the micelle number and proportion in the colloidal structure increased [20,21]. Based on the results of these analyses, there is a consensus that a rejuvenator can effectively control and reduce the performance loss of recycled asphalt after aging and change the colloidal structure of aged asphalt [22].…”
Section: Introductionmentioning
confidence: 99%
“…et al and Bilema, M. et al [17][18][19] surveyed the influence of rejuvenator content on penetration, softening point and ductility of recycled asphalt. Researchers investigated the microscopic mechanism of aged asphalt with rejuvenator, and it was found that the composition of aged asphalt changed by the rejuvenator, the light components decreased and the micelle number and proportion in the colloidal structure increased [20,21]. Based on the results of these analyses, there is a consensus that a rejuvenator can effectively control and reduce the performance loss of recycled asphalt after aging and change the colloidal structure of aged asphalt [22].…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopically, the dynamic shear rheological (DSR) experiment can be used to analyze the significant effects of time, temperature, asphalt variety, and rejuvenator on composite shear modulus by means of variance analysis, so as to compare their effects on diffusion [31][32][33][34]. On the micro level, infrared spectrum analysis, gel chromatography, thin layer chromatography, Fourier infrared spectroscopy and other advanced means are adopted to study asphalt mixture, and molecular simulation technology is used to simulate the diffusion behavior of old and new asphalt [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%